2016
DOI: 10.1002/fuce.201500137
|View full text |Cite
|
Sign up to set email alerts
|

Defect Detection in Fuel Cell Gas Diffusion Electrodes Using Infrared Thermography

Abstract: Polymer electrolyte membrane fuel cells are energy conversion devices that offer high power densities and high efficiencies for mobile and other applications. Successful introduction into the marketplace requires addressing cost barriers such as production volumes and platinum loading. For cost reduction, it is vital to minimize waste and maximize quality during the manufacturing of platinum-containing electrodes, including gas diffusion electrodes (GDEs). In this work, we report on developing a quality contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Monitoring defects in the CCM within an MEA is complicated by the fact that it is contained within the GDL layers. In this case, IR thermography has been shown to be effective at characterizing defects . In this study, we use IR thermography to examine the cathode side of an MEA, as shown in the schematic side view in Figure A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Monitoring defects in the CCM within an MEA is complicated by the fact that it is contained within the GDL layers. In this case, IR thermography has been shown to be effective at characterizing defects . In this study, we use IR thermography to examine the cathode side of an MEA, as shown in the schematic side view in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…These IR results shows that these defects are also significant and should be of concern prior to MEA assembly. Although the hotspot defects do not initially appear to affect performance, they can potentially grow during cell operation and eventually cause shutdown of the PEMFC …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For RFT, a nonflammable (< 4% H 2 ) reactive mixture of H 2 /O 2 in N 2 is flowed through the GDE where the catalytic reaction on the Pt surface generates heat, creating a measurable thermal signature. A proof-of-concept of the extension of the RFT technique to an open-atmosphere environment, where the GDE is conveyed on a bench-top roller system, was previously reported and termed as reactive impinging flow (RIF) [25]. In this work, we report on the further development of the IR thermography technique coupled with RIF to detect defects in moving GDEs.…”
Section: Introductionmentioning
confidence: 98%
“…Compared to the prior modeling work of RFT [10], the model developed in this work captures the physics of impinging flow onto the porous GDE on a moving webline. Moreover, this manuscript builds upon RIF technique demonstration [25] and explores optimal parametric space for webline velocity, gas flowrate, composition, and defect geometry for defect detectability. It also provides recommendations for improved defect detection using RIF technique.…”
Section: Introductionmentioning
confidence: 99%